Community-Based Follow-Up After NICU Discharge: A Practice-Focused Narrative Review of Nursing and Midwifery Care for Preterm Infants - Vikentia Harizopoulou; Angeliki Bolou; Evdoxia Tsiakiri; Maria Bouroutzoglou; Victoria Vivilaki; Dimitra Metallinou (Pediatric Reports, 2026)
Background/Objectives: Preterm birth remains a significant global public health challenge, associated with increased morbidity, rehospitalisation, and long-term vulnerability. The transition from the neonatal intensive care unit (NICU) to the home environment represents a critical phase. This practice-focused narrative review synthesises current evidence on community-based post-discharge follow-up for preterm infants, with particular emphasis on the complementary contribution of community health nursing and midwifery within multidisciplinary follow-up models, endocrine-metabolic surveillance and coordinated care for medically complex infants. Methods: A narrative synthesis of review articles, clinical guidelines, and empirical studies published between 2016 and 2026 was undertaken. Searches were performed in PubMed, Scopus, and CINAHL using terms related to preterm birth, NICU discharge, community follow-up, family-centred care, community health nursing, midwifery, and metabolic disorders. Results: Community-based, family-centred follow-up programmes are associated with improved continuity of care, increased parental confidence, enhanced breastfeeding outcomes, and reduced healthcare utilisation. Community health nurses, midwives and health visitors contribute complementary expertise within multidisciplinary follow-up by coordinating continuity of care, providing clinical surveillance of growth and feeding, supporting caregiver education, facilitating early identification of complications, and ensuring timely referral. However, endocrine and metabolic vulnerabilities remain underrepresented in many follow-up models, while infants with complex healthcare needs require individualised, risk-stratified surveillance. Conclusions: Community-based, interdisciplinary, and family-centred follow-up after NICU discharge is essential to enhance the quality and safety of care for preterm infants. Integrated, risk-stratified models of follow-up that combine preventive surveillance, family education, multidisciplinary coordination, and continuity of care may facilitate earlier recognition of complications and improve long-term outcomes.